Multidrug resistant tuberculosis (MDR-TB): an update - Tiberi, Simon (Henry Stewart Talks, 2021)
Update on the global situation, MDR-TB in 2020, How MDR-TB is currently managed, Treatment principles and strategies, Latest WHO categorization of anti-MDR-TB drugs, Further developments, Global TB network